Legal Protection for Indonesian Ship Crews in the Free Seas - Putra, Ananda Fadhila Perkasa; Anggraeny, Arianty; Said, Muhammad Fachri (HORIZON PUBLIC LEGAL STUDIES, 2024)
This study aims to indentify and analyze the efforts of the Indonesian Government in providing protection to Indonesian crew members on the high seas and to identify and analyze the constraints faced by the Indonesian government in providing protection to Indonesian crew members on the high seas. This type of research is normative legal research because it operates simultaneously on legal principles, legal norms, rules of legislation, and doctrine. By researching library materials that use the object of the study in the form of existing libraries, both sourced from books, magazinez, and regulations that have a correlation to the discussion of the problem, so this writing is also library research. The results of this study indicate that the laws and regulations overlap between one regulation and another, causing legal uncertainly which results in protection for crew members which is difficult to guarantee. Abstrak Penelitian ini bertujuan untuk mengetahui dan menganalisis Upaya Pemerintah Indonesia dalam memberikan perlindungan kepada Anak Buah Kapal Indonesia di laut bebas dan untuk mengetahui dan menganalisis Kendala-kendala yang dihadapi oleh Pemerintah Indonesia dalam pemberian perlindungan terhadap Anak Buah Kapal Indonesia di laut bebas. Jenis Penelitian ini adalah penelitian hukum normatif karena dengan mengoperasikan secara bersamaan asas-asas hukum, norma hukum, kaidah dari perundang-undangan, dan doktrin. Dengan cara meneliti bahan pustaka yang menggunakan objek kajian berupa pustaka yang ada, baik bersumber dari buku, majalah, dan peraturan-peraturan yang memiliki korelasi terhadap pembahasan masalah, sehingga penulisan ini juga bersifat penelitian pustaka (Library Research). Hasil penelitian ini menunjukkan bahwa peraturan perundang-undangan mengalami tumpang tindih antara peraturan yang satu dengan yang lainnya sehingga menimbulkan ketidakpastian hukum yang berakibat kepada perlindungan bagi anak buah kapal yang sulit untuk dijamin.